Peran Strategi Pemasaran Viral Dalam Memprediksi Niat Pembelian Produk Fashion Ramah Lingkungan Pada Pelanggan Gen-Z - gosal, Michelle; Lesmana, Kylie; Wiander, Bryan; Molina, Natanael T; Djiemesha, Novicha; syam, Asriah (Jurnal Online Manajemen ELPEI, 2025)
This study aims to determine the influence of customer interest in purchasing environmentally friendly products and customer awareness behavior in buying ecofriendly products, especially in the fashion sector. This research employs a quantitative method with a population drawn from several cities in Indonesia using Purposive Sampling. The operational indicators include Entertainment, Informativeness, Irritation, and Source Credibility. Respondents must have watched the viral campaign mentioned in the questionnaire. Partial Least Squares Structural Equation Modeling (SEM-PLS) was used to identify underlying patterns in the data and gain a deeper understanding of the relationships between variables. The results show that these four indicators influence purchase intention but the impact is small and less significant. This is due to the majority of respondents being Generation Z, who are not yet fully aware of their surrounding environment. Although these indicators manage to capture Gen Z's attention, they have not yet succeeded in changing their mindset towards purchasing environmentally friendly products. Key Words : Eco-friendly products; Purchase intention; Customer consciousness; Viral marketing.